CARD14/CARMA2 Signaling and its Role in Inflammatory Skin Disorders - Zotti, Tiziana; Polvere, Immacolata; Voccola, Serena; Vito, Pasquale; Stilo, Romania (Frontiers in Immunology, 2018)
CARMA proteins represent a family of scaffold molecules which play several crucial biological functions, including regulation of immune response and inflammation, tissue homeostasis, and modulation of G-Protein Coupled Receptor (GPCR) signaling. Among the CARMA proteins, CARD14/CARMA2 and its alternatively spliced isoforms are specifically expressed in epithelial cells and keratinocytes. Recent evidences have shown that CARD14/CARMA2 mediates induction of inflammatory response in keratinocytes, and that mutations in CARD14/CARMA2 gene segregate with familial transmission of chronic inflammatory disorders of the human skin. Similarly to CARD11/CARMA1 and CARD10/CARMA3, CARD14/CARMA2 signaling occurs trough formation of a trimeric complex which includes BCL10 and MALT1 proteins. However, it is becoming increasingly evident that in addition to the CBM complex components, a number of accessory molecules are able to finely modulate the signals conveyed on and amplified by CARD14/CARMA2. The study of these molecules is important both to understand the molecular mechanisms that underlie the role of CARMA2 in keratinocytes and because they represent potential therapeutic targets for the development of therapeutic strategies aiming at the treatment of inflammatory diseases of the human skin. In this review, we provide an overview on the molecular mechanisms mediating CARD14/CARMA2 signaling and its implication in our understanding of the pathogenesis of human inflammatory skin disorders.